Niat Menjadi Whistleblower pada Mahasiswa Akuntansi : Pengujian Theory of Planned Behavior (Studi pada Mahasiswa S-1 Akuntansi Universitas Bengkulu) - Firman Setiawan; Lisa Martiah Nila Puspita (UNIB Press, 2022)
This study aimend to analyze the influence of intention whistleblower of accounting student : with theory of planned behavior (study of accounting student Bengkulu University). The population in this study are student of accounting from Bengkulu University periode 2017-2018 . This type of research used in this research in the empirical research. The sampling technique used was purposive sample and selected 60 respondent. Data analysis tools in this test using IBM SPSS version 25, which wants to see the effect of attitude toward behavior, subjective norm, and perceived behavior control against the intention whistleblower. The results of this study indicate that attitude toward behavior has a positive effect on intention whistleblower, subjective norm has a positive effect on intention whistleblower, and perceived behavior control has a positive effect on intention whistleblower. This study aimend to analyze the influence of intention whistleblower of accounting student : with theory of planned behavior (study of accounting student Bengkulu University). The population in this study are student of accounting from Bengkulu University periode 2017-2018 . This type of research used in this research in the empirical research. The sampling technique used was purposive sample and selected 60 respondent. Data analysis tools in this test using IBM SPSS version 25, which wants to see the effect of attitude toward behavior, subjective norm, and perceived behavior control against the intention whistleblower. The results of this study indicate that attitude toward behavior has a positive effect on intention whistleblower, subjective norm has a positive effect on intention whistleblower, and perceived behavior control has a positive effect on intention whistleblower.